PricewaterhouseCoopers guide to charitable giving - Kennedy, Michael B. (John Wley & Sons, 2002)
PricewaterhouseCoopers’ Guide to Charitable Giving addresses the many tax aspects of charitable giving by walking you through the rules of charitable giving and their relationship to your taxes. This indispensable guide explores different charitable giving alternatives, focusing on current gifts, deferred or planned gifts, gifts of income, annuities, and charitable bequests. It also covers the advantages and disadvantages of each type of gift, as well as funding alternatives and assets that may be utilized. The charitable giving strategies discussed are supplemented with essential forms, their instructions, and relevant IRS publications